Relaxation, Percolation, and Non-Spontaneous Fluctuation of Linguistic Behavior in a Quasi-Isolated System - Tilsen, Sam (Frontiers in Physics, 2022)
Linguistic behaviors arise from strongly interacting, non-equilibrium systems. There is a wide range of spatial and temporal scales that are relevant for the analysis of speech. This makes it challenging to study language from a physical perspective. This paper reports on a longitudinal experiment designed to address some of the challenges. Linguistic and social preference behavior were observed in an ad-hoc social network over time. Eight people participated in weekly sessions for ten weeks, playing a total of 535 map-navigation games. Analyses of the degree of order in social and linguistic behaviors revealed a global relaxation toward more ordered states. Fluctuations in linguistic behavior were associated with social preferences and with individual interactions.